Improving learning outcomes in slagball material through the project-based learning model in grade IV at SD Negeri Gondang II Bojonegoro - Moh. Nurkholis; Junaidi, Slamet; Zawawi, M. anis; Setiawan, Irwan (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This action research aims to improve the quality of teaching practices, address real issues in the classroom, and enhance teachers' professional development. It also seeks to foster students' mindsets so they can grow and achieve the desired learning outcomes. The research used the Project-Based Learning (PBL) method and was conducted in two cycles, with each cycle consisting of two sessions. Prior to the research, data showed that out of 14 students, 2 were actively engaged (10%), 4 were fairly active (25%), and 9 were less active (69%). In the second cycle, student activity improved, with 9 students being active (25%) and 6 students moderately active (68%). Regarding teacher activity, the first cycle showed a score of very good (14.28%), good (45.71%), and sufficient (17.14%). In the second cycle, the teacher's performance improved, with very good (42.85%), good (34.28%), and sufficient (8.57%), but the learning outcomes still did not meet the Minimum Completion Criteria (KKM). The findings indicate that the PBL approach positively impacted student activity and teacher performance, although there is still room for improvement to fully meet the KKM standards